2015
DOI: 10.1038/pr.2015.41
|View full text |Cite
|
Sign up to set email alerts
|

Phlebotomy-induced anemia alters hippocampal neurochemistry in neonatal mice

Abstract: Background Phlebotomy-induced anemia (PIA) is common in preterm infants. The hippocampus undergoes rapid differentiation during late fetal/early neonatal life and relies on adequate oxygen and iron to support oxidative metabolism necessary for development. Anemia shortchanges these two critical substrates, potentially altering hippocampal development and function. Methods PIA (hematocrit <25%) was induced in neonatal mice pups from postnatal day (P)3 to P14. Neurochemical concentrations in the hippocampus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…However, as many gut resident immune cells, including macrophages, do not circulate, sampling preterm infants for gut resident macrophage number and function, in addition to direct evaluation of intestine barrier activity during the development of anemia is not currently feasible. As a result, we decided to complement this study with a previously validated pre‐clinical model of PIA to directly evaluate the impact of anemia on intestine immunity and barrier function . However, even in this model, significant barriers exist, as the size and overall cellular availability of individual mouse pups limit the scope of analysis that can be accomplished in this setting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, as many gut resident immune cells, including macrophages, do not circulate, sampling preterm infants for gut resident macrophage number and function, in addition to direct evaluation of intestine barrier activity during the development of anemia is not currently feasible. As a result, we decided to complement this study with a previously validated pre‐clinical model of PIA to directly evaluate the impact of anemia on intestine immunity and barrier function . However, even in this model, significant barriers exist, as the size and overall cellular availability of individual mouse pups limit the scope of analysis that can be accomplished in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, sample volume limitations in both clinical and animal studies of neonatal immune function have likely contributed to challenges associated with conducting studies that produce a level of understanding in neonates comparable to that obtained from similarly conducted studies in adult mice and patients clinically. Importantly, the rate of anemia employed in this study was designed to match the rate observed in many patients and does not induce detectable changes in heart rate or the development of acidosis that would be expected to occur in the setting of significant hemodynamic alterations/shock . While nearly all pups reached our threshold of severe anemia (25% Hct) on P7, followed by analysis of the potential impact of anemia the following day, future studies will be necessary to examine the effects of extended anemia exposure and threshold variations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations